Machinery traffi c and cover crop eff ects on water infi ltration rate in a Xanthic Hapludox - Garcia Neto, Ernani; Caldas Umburanas, Renan; Hugo Outeiro, Vitor; Marques Lopes Müller, Marcelo; Rampim, Leandro; Antonio Tormena, Cassio; Andre Pott, Cristiano (Revista Ciência Agronômica, 2023)
The eff ects of machinery traffi c and cover crops on soil physical properties have been underexplored under no-till agricultural production in subtropical environments. The objective of this study was to quantify the soil water infi ltration rate and related soil physical properties in response to tractor traffi c levels (0, 2, 5, and 20 passes) and the presence or absence of cover crops in a Xanthic Hapludox soil over two growing seasons under no-till conditions. The experiment was carried out in a randomized block design arranged in a factorial scheme with four replications. The traffi c factor was constituted by the number of passes with a 6 Mg weight tractor. The winter crop management practices factor consisted of the cover crops (i) black oat (Avena strigosa) in 2017 and turnip (Raphanus sativus var. oleiferus) in 2018 compared with (ii) fallow with spontaneous vegetation. The soil water infi ltration rate increased with cover crops when compared to fallow. Regarding tractor traffi c levels, shortly after soil compaction, there was a lower water infi ltration rate at 20 passes, 45 mm h-1 lower than the absence of tractor traffi c. The soil water infi ltration rate was positively correlated with macroporosity and negatively correlated with soil bulk density. After 14 months of soil compaction caused by tractor traffi c, an improvement in the soil physical properties and the water infi ltration rate was found, which were enhanced by the inclusion of cover crops.